2018
DOI: 10.1111/mcn.12680
|View full text |Cite
|
Sign up to set email alerts
|

Developing a core outcome set for childhood obesity prevention: A systematic review

Abstract: Synthesis of effects of infant feeding interventions to prevent childhood obesity is limited by outcome measurement and reporting heterogeneity. Core outcome sets (COSs) represent standardised approaches to outcome selection and reporting. The aim of this review is to identify feeding outcomes used in infant feeding studies to inform an infant feeding COS for obesity prevention interventions. The databases EMBASE, Medline, CINAHL, CENTRAL, and PsycINFO searched from inception to February 2017. Studies eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…We reviewed pediatric literature related to MCAD deficiency and PKU to identify the scope of reported and recommended outcomes. Similar to reviews of outcomes reporting in other clinical areas [26][27][28], we found substantial diversity of outcomes reported across the five core areas of outcome measurement for both diseases. Notably, almost a third of outcomes for MCAD deficiency and over 15% for PKU were reported in only a single study.…”
Section: Discussionsupporting
confidence: 74%
“…We reviewed pediatric literature related to MCAD deficiency and PKU to identify the scope of reported and recommended outcomes. Similar to reviews of outcomes reporting in other clinical areas [26][27][28], we found substantial diversity of outcomes reported across the five core areas of outcome measurement for both diseases. Notably, almost a third of outcomes for MCAD deficiency and over 15% for PKU were reported in only a single study.…”
Section: Discussionsupporting
confidence: 74%
“…The early introduction of solids increases the risk of diarrheal disease, food allergies, and probably increases the rate of being overweight in infancy and childhood [6,7]. It is estimated that worldwide there are 41 million children under five years old who are obese or overweight, and recent reviews have strengthened the reported association between the early introduction of solids, particularly introduction before the age of four months, and higher protein foods and obesity [8,9,10,11]. The gastrointestinal microbiome is influenced by early infant feeding practices, including the early introduction of complementary foods.…”
Section: Introductionmentioning
confidence: 99%
“…Parent/carer response to their infant's needs during feeding requires an understanding of their infant's communication. However, a recent systematic review of infant feeding interventions discussed limited evidence on parent/caregiver knowledge concerning responsive feeding practices (Matvienko‐Sikar et al, ). Responsive feeding has been suggested as a learned behaviour between the dyad and is a reciprocal activity (Appleton et al, ; Oxford, & Findlay, D.…”
Section: Discussionmentioning
confidence: 99%